The characterization of four gene expression analysis in circulating tumor cells made by Multiplex-PCR from the AdnaTest kit on the lab-on-a-chip Agilent DNA 1000 platform - Škereňová, Markéta; Mikulová, Veronika; Čapoun, Otakar; Zima, Tomáš (Biochemia medica, 2016)
INTRODUCTION: Nowadays, on-a-chip capillary electrophoresis is a routine method for the detection of PCR fragments. The Agilent 2100 Bioanalyzer was one of the first commercial devices in this field. Our project was designed to study the characteristics of Agilent DNA 1000 kit in PCR fragment analysis as a part of circulating tumour cell (CTC) detection technique. Despite the common use of this kit a complex analysis of the results from a long-term project is still missing. MATERIALS AND METHODS: A commercially available Agilent DNA 1000 kit was used as a final step in the CTC detection (AdnaTest) for the determination of the presence of PCR fragments generated by Multiplex PCR. Data from 30 prostate cancer patients obtained during two years of research were analyzed to determine the trueness and precision of the PCR fragment size determination. Additional experiments were performed to demonstrate the precision (repeatability, reproducibility) and robustness of PCR fragment concentration determination. RESULTS: The trueness and precision of the size determination was below 3% and 2% respectively. The repeatability of the concentration determination was below 15%. The difference in concentration determination increases when Multiplex-PCR/storage step is added between the two measurements of one sample. CONCLUSIONS: The characteristics established in our study are in concordance with the manufacturer's specifications established for a ladder as a sample. However, the concentration determination may vary depending on chip preparation, sample storage and concentration. The 15% variation of concentration determination repeatability was shown to be partly proportional and can be suppressed by proper normalization.
Keywords: Gene Expression Regulation, Neoplastic; lab-on-a-chip devices; Male; Actins; circulating tumour cells; antigeny povrchové; Reagent Kits, Diagnostic; glutamátkarboxypeptidasa II; Neoplastic Cells, Circulating; Multiplex Polymerase Chain Reaction; regulace genové exprese u nádorů; DNA nádorová; Lab-On-A-Chip Devices; Glutamate Carboxypeptidase II; capillary electrophoresis; nádorové cirkulující buňky; mužské pohlaví; Prostatic Neoplasms, Castration-Resistant; nádory prostaty rezistentní na kastraci; reprodukovatelnost výsledků; aktiny; Reproducibility of Results; DNA, Neoplasm; multiplexová polymerázová řetězová reakce; laboratoř na čipu; prostatický specifický antigen; lidé; Humans; Antigens, Surface; erbB receptory; multiplex PCR; Agilent DNA 1000 kit; reagenční diagnostické soupravy; ErbB Receptors; Biomarkers, Tumor; nádorové biomarkery; Prostate-Specific Antigen